Cerebral Fat Migration After Spine Surgery - Dries Vanhoegaerden; Michiel Herteleer; Philippe Demaerel (Journal of the Belgian Society of Radiology)
A 73-year-old patient with a complex sacral fracture underwent stabilising orthopaedic surgery. Postoperative brain CT showed fat droplets in the subarachnoid space and lateral ventricle. These fat droplets migrated into the cerebrospinal fluid by a tear in the sacral thecal sac. Teaching point: Intracranial subarachnoid fat droplets may be observed after spinal surgery.